how do i answer that I don't even know that sorry
Answer:
mean=average which means you add all of the numbers and divide by the number of numbers there are, which sounds pretty confusing, but i'll show you! 9+7+11+10+8=45, now you divide 45 by 5, which is how many numbers there are that we had to add. 45 divided by 5 is 9, which means the MEAN/average is 9!
Step-by-step explanation:
hope this helps!
Answer
Of is Multiplication I believe
Step-by-step explanation:
Of is multiplication
Part A
We have
![f\left(x\right)=\left(x+3\right)^2-1](https://tex.z-dn.net/?f=f%5Cleft%28x%5Cright%29%3D%5Cleft%28x%2B3%5Cright%29%5E2-1)
. To solve for the x-intercept, we set f(x) equal to 0. That is
![\left(x+3\right)^2=1](https://tex.z-dn.net/?f=%5Cleft%28x%2B3%5Cright%29%5E2%3D1)
Take the square root of both sides,
The x-intercept is (-2,0).
To solve for the y-intercept, we set x=0. That is
The y-intercept is (0, 8)
The coordinates of the optimum point are actually the vertex which can be easily seen from the vertex form equation given above. The minimum point is
(-3, -1).
Part B.
We have
![g\left(x\right)=-2x^2+8x+3](https://tex.z-dn.net/?f=g%5Cleft%28x%5Cright%29%3D-2x%5E2%2B8x%2B3)
.
Factor out -2
![=-2\left(x^2-4x\right)+3](https://tex.z-dn.net/?f=%3D-2%5Cleft%28x%5E2-4x%5Cright%29%2B3)
Complete the square
![=-2\left(x^2-4x+4\right)+3-2\left(4\right)](https://tex.z-dn.net/?f=%3D-2%5Cleft%28x%5E2-4x%2B4%5Cright%29%2B3-2%5Cleft%284%5Cright%29)
Simplify
![g(x)=-2\left(x-2\right)^2-5](https://tex.z-dn.net/?f=g%28x%29%3D-2%5Cleft%28x-2%5Cright%29%5E2-5)
Part C
We have
![h\left(t\right)=-16t^2+28t](https://tex.z-dn.net/?f=h%5Cleft%28t%5Cright%29%3D-16t%5E2%2B28t)
.
The maximum height is 12.25 feet after 0.875 seconds from the time of the jump. The dolphin will be back in the water after 1.75 seconds. The graph of the jump is shown in the photo.
Answer:
1. ![(a + 3)(5a-14)](https://tex.z-dn.net/?f=%28a%20%2B%203%29%285a-14%29)
2. ![(p^2-6)[1-q(p^2-6)]](https://tex.z-dn.net/?f=%28p%5E2-6%29%5B1-q%28p%5E2-6%29%5D)
Step-by-step explanation:
1. The first thing to do to factor the expression is to take the expression (a + 3) as a common factor with its lowest exponent.
Then the expression.
remains as:
![(a + 3)(5 (a + 3) -1)\\\\(a + 3)(5a +15 -1)\\\\(a + 3)(5a-14)](https://tex.z-dn.net/?f=%28a%20%2B%203%29%285%20%28a%20%2B%203%29%20-1%29%5C%5C%5C%5C%28a%20%2B%203%29%285a%20%2B15%20-1%29%5C%5C%5C%5C%28a%20%2B%203%29%285a-14%29)
2. The first thing to do to factor the expression is to take the expression
as its common factor with its lowest exponent.
Then the expression
remains as:
![(p^2-6)[1-q (p^2-6)]](https://tex.z-dn.net/?f=%28p%5E2-6%29%5B1-q%20%28p%5E2-6%29%5D)